SYNTHESIS OF CHITOSAN/TiO2 COMPOSITE AND ITS COATING ON SURFACE OF TEXTILE SUBSTRATE - Agung Nugroho Catur Saputro (Molekul, 2016)
Coatings of composite Chitosan/TiO2 on a surface of textile have been successfully performed. These coatings were done by dip-coating method. The variety of coatings textile were performed in 2, 4, and 6 coatings. The textile was coated by composite of Chitosan/TiO2 then characterized by FTIR Spectrometry, X-Ray Diffraction and Scanning Elelectron Microscopy (SEM). Based on the spectra of FTIR Spectrofotometry, XRD difractogram and imaging of SEM it can be concluded that hypothesized composite of Chitosan/TiO2 was coated on surface of textile but that hypothesis were still very weak and it need to be examined by performance test.